THE INFLUENCE OF ENTREPRENEURIAL INTERNAL AND EXTERNAL FACTORS ON THE SUSTAINABILITY OF THE ORGANIC VEGETABLE BUSINESS DURING THE COVID-19 PANDEMIC - Sepriani, Wiwi; Nuswantara, Bayu; Maria, Maria (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2023)
The organic vegetable business is a business that has high opportunities. The real conditions experienced during the Covid-19 pandemic harmed farmers who were also in the organic vegetable business, namely a 50 percent decrease in sales. A sustainable agricultural business depends on the entrepreneurial spirit possessed by agribusiness actors. This study aims to analyze the influence of entrepreneurial internal and external factors on the sustainability of the organic vegetable business with business performance as an intervening variable. This research was carried out from October to December 2022 in Batur Village, Getasan District. The type of research used in this research is descriptive quantitative, with primary and secondary data types. The sample used is 100 respondents, taken by nonprobability sampling with the purposive method. Data analysis techniques used by researchers are structural equation modeling (SEM) and partial least squares path modeling (PLS-SEM). The results of this research are entrepreneurial internal factors (X1) with p-value 0,003 and entrepreneurial external factors (X2) with p-value 0,000 have a significant and significant positive effect on the sustainability of the organic vegetable business (Y2). But entrepreneurial internal factors (X1) with p-value 0,117 and entrepreneurial external factors (X2) with p-value 0,122 have no significant effect on business sustainability (Y2) through business performance (Y1) as intervening variables. Therefore, if everyone improves business performance personally it will distrupt business performance in the group.